Topical Application of Herbal Mixture Extract Inhibits Ovalbumin- or 2, 4-Dinitrochlorobenzene-Induced Atopic Dermatitis. (5th December 2012) - Kim, Soon Re; Choi, Han-Seok; Seo, Hye Sook; Choi, Youn Kyung; Shin, Yong Cheol; Ko, Seong-Gyu
Abstract : KM110329 is four traditional herbal medicine mixtures with anti-inflammatory properties. Atopic dermatitis (AD) is an inflammatory skin disease associated with enhanced T-helper2 (Th2) lymphocyte response to allergens that results in elevated serum eosinophil and Immunoglobulin E (IgE) levels and leukocyte infiltration in atopic skin sites. In this study, we investigated the effect of topical application of KM110329 ethanol extract on the ovalbumin (OVA) or 2, 4-dinitrochlorobenzene- (DNCB-) induced AD mouse models. For that purpose, we observed the effects of KM110329 on blood eosinophils, skin mast cells, production of serum IgE, and expression of cytokine mRNA in the atopic dermatitis skin lesions of OVA allergen- or DNCB-treated BALB/c mice. KM110329 significantly reduced blood eosinophils cell numbers in OVA or DNCB-treated BALB/c mice. Histological analyses demonstrated decreased mast cell count as well as dermal infiltration by inflammatory cells. In the skin lesions, mRNA expression of interleukine (IL)-4, IL-13, and IL-17 was inhibited by KM110329. KM110329 also suppressed the production of serum IgE level in both the OVA- and DNCB-induced atopic dermatitis model. Taken together, our results showed that topical application of KM110329 extracts exerts beneficial effects in AD symptoms, suggesting that KM110329 might be a useful candidate for the treatment of AD.